Peningkatan Penguasaan Konsep Matematika Melalui Model Pembelajaran Kooperatif Tipe STAD - Aswin Saputra; Ade Lukman Nulhakim (Universitas Indraprasta PGRI Jakarta, 2017)
The purpose of this research is to know the increase in concept mastery of students class VIII-2 through STAD type cooperative learning model in MTs Negeri 40, West Jakarta. The method used in this research is a qualitative approach with a classroom action research technique, which is an action performed by the teacher to improve teaching by making changes and studying the consequences of the changes. Techniques used in data collection are: end of cycle test and observation. The results show that the process of learning mathematics with the application of STAD type cooperative model can make student’s learning outcomes better. The result obtained is the absorption class in cycle I is 51.163%, then repaired in cycle II with the absorption class of 90.69%. This shows progress that the students have obtained good learning outcomes from cycle I.